English academy football practitioners` perceptions of training load, maturation and injury risk: A club case study - Johnson, D.; Williams, S.; Bekker, S.; Bradley, B.; Cumming, S. (International Journal of Sports Science & Coaching, 2024)
The management of training load in youth team-sport athletes is important. There is, however, a lack of research on practitioners` perceptions and understandings of managing training load during this period and what this means in terms of maturational status and injury risk. This study aimed to investigate academy football practitioners` perceptions and understanding of training load, maturation and injury risk in young male footballers. Coaches, sports scientists, medical staff and key stakeholders from a professional football club academy in England participated in focus groups investigating their understanding and perceptions of training load, maturation and injury risk. A qualitative descriptive methodology utilising framework analysis was used to capture and better understand participants` views. Findings revealed that practitioners consider managing training load during adolescence to be comprised of, and mediated by, three key elements: club philosophy, factors inside the club's control (periodisation strategy; staff member practice), and factors outside the club's control (life load; growth and maturation). This study is an important addition to the current literature on managing injuries through the growth spurt by investigating how different stakeholders perceive training load, maturation and potential strategies to mitigate risk.